Ependymal tumours in childhood: outcomes and prognostic factors - Nkosi, Zanele (Division of Radiation Oncology, 2018)
OBJECTIVES: To retrospectively review the patient demographics, disease profile and treatment outcomes of paediatric patients treated for ependymoma at our institution. STUDY DESIGN AND METHODS: 51 eligible patients were treated between 1980 and 2013. The median age at presentation was 6 years. The majority of patients were male (66,7%), had infratentorial tumours (62,7%) and had low-grade tumours (70,6%). Gross total resection (GTR) was achieved in 22 patients (43,1%). Thirtyeight patients received adjuvant radiotherapy (76,5%) and 10 (19,6%) received adjuvant chemotherapy. RESULTS: The 5-year overall survival (OS) was 63,3 % (median follow up of 46 months). The 5 year progression free survival (PFS) was 50,70%. Seventeen (33,3%) patients experienced treatment failure, of which 13 (76,5%) represented local failure. The median time to first relapse was 20 months. The 5 year PFS for children > 3 was 50,0 % and 27,7% for children ≤ 3 years of age (p = 0.0356). GTR had a superior 5- year OS of 73,9% over subtotal resection with a value of 56,7% (p = 0.0016). Similarly an improved 5-year PFS of 70,3% versus 29,1% was observed with GTR over subtotal resection (p = <0.0001). Patients who received adjuvant radiotherapy (RT) had significantly better outcomes than those in whom RT was not given (p = <0.0001, 5 year OS of 69,7% versus 37,5%). CONCLUSION: This review confirms the finding that GTR is associated with improved outcomes and that adjuvant radiation therapy positively impacts survival. The worse outcomes in the younger age group requires further evaluation and possible change in treatment protocol for this group of patients.